(untitled) - Nguyen, Thi Thanh Mai (Cần Thơ, 2010)
This study was conducted with a descriptive approach to determine if the webquest could promote academic autonomy and to investigate student's attiudes about the webquest in English as foreign language.
Keywords: Learner autonomy,Tự học,English language,Tiếng Anh; Study and teaching,Dạy và học